Evaluación de cuatro métodos de propagación asexual del maracuyá passiflora edulis - Cango Aguilar, Jaime (2006)
In Santa Inés farm from Machala University during the time from No-vember to January of 2006. It was investigated about the asexual pro-pagatión of the maracuyá Passiflora edulis. The objectives said in this investigation were: 1. Evaluation of four methods of asexual propaga-tion. 2. Establish the mast efficient comparative method based on an economic analisis. The four of asexual propagation investigated and that constitied were: Supporting aerial, Supporting serpentarios, esquejes and inherts. For the supporting aerial was made a sponge, saturated in smake, liquids and raizal, commercial productsrich in Nitrogen and phosphoros.In the base part of the selected guide, an incision was made in the bark to apply the Hormonagro Sour naf-talenacético carrier product of aux-inas ( naftalenacetico acid ) also the auxina is used in the extreme cases of the esquejes. With the supporting serpentarios, we also used it with the hormonal product. Produced the lightning of the supporting. It was transplanted to bags of polietileno with a sustract of floor- sand – smoke. The treatments were assigned in the camp following a mathe-matical model of the design with blocks with five copies. The experi-mented unities were made by ten plants. The varieties analized were: percentages of lighthing, days of rooting, days of the lighthing of the inhert, the vegetative unrolling, percentage of roots, days of the transplant. The analisis of varieties threw high significants for the treatments in all the varieties studied, from the treatments investigated with the sup-porting aerial, we achieved the best average of lighthing with a 100 % of supporting that made it root and developed reaching the highest height at transplantation.